Safety and Transcriptome Analysis of Live Attenuated Brucella Vaccine Strain S2 on Non-pregnant Cynomolgus Monkeys Without Abortive Effect on Pregnant Cynomolgus Monkeys - Sun, Shijing; Jiang, Hui; Li, Qiaoling; Liu, Yufu; Gao, Qiang; Liu, Wei; Qin, Yuming; Feng, Yu; Peng, Xiaowei; Xu, Guanlong; Shen, Qingchun; Fan, Xuezheng; et al. (Frontiers in Veterinary Science, 2021)
Brucellosis, caused by Brucella spp, is an important zoonotic disease leading to enormous economic losses in livestock and posing a great threat to public health worldwide. The live attenuated Brucella suis (B. suis) strain S2, a safe and effective vaccine, is widely used in animals in China. However, S2 vaccination in animals may raise debates and concerns in terms of safety to primates, particularly humans. In this study, we used cynomolgus monkey as an animal model to evaluate the safety of the S2 vaccine strain on primates. In addition, we performed transcriptome analysis to determine gene expression profiling on cynomolgus monkeys immunized with the S2 vaccine. Our results suggested that the S2 vaccine was safe for cynomolgus monkeys. Transcriptome analysis identified 663 differentially expressed genes (DEGs), of which 348 were significantly up-regulated and 315 were remarkably down-regulated. Gene Ontology (GO) classification and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis indicated that these DEGs were involved in various biological processes, including chemokine signaling pathway, actin cytoskeleton regulation, defense response, immune system processing, and type I interferon signaling pathway. The molecular functions of the DEGs were mainly comprised of 2'-5'-oligoadenylate synthetase activity, double-stranded RNA binding and actin-binding. Moreover, the cellular components of these DEGs included integrin complex, myosin II complex, and blood microparticle. Our findings alleviate the concerns over the safety of the S2 vaccine on primates and provide a genetic basis for mammalian host response following vaccination with the S2 vaccine.